Preparation method and application of regenerated PET-based hybrid xerogel

The preparation of a PET-based hybrid xerogel with Ni@CNT and PEG integration addresses the limitations of existing PET recycling by creating a multifunctional composite material with enhanced mechanical strength and photothermal conversion, while reducing environmental impact.

CN119219968APending Publication Date: 2024-12-31CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458236.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing PET recycling methods face challenges in achieving high recycling rates, environmental pollution, and limited functionality of PET-based composite materials, with chemical recycling being complex and physical recycling lacking multi-functionality.

Method used

A method is developed to prepare a PET-based hybrid xerogel using dissolution crystallization inducing gelation, incorporating functional nanofillers like Ni@CNT, and enhancing with phase change material PEG to create a multifunctional composite material with improved mechanical strength and electromagnetic shielding and photothermal conversion capabilities.

Benefits of technology

The method effectively recycles waste PET into a hybrid xerogel with high mechanical strength, efficient photothermal conversion, and effective electromagnetic shielding, addressing environmental pollution and enhancing resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of regenerated PET-based hybrid xerogel and application of a PET-based multifunctional composite material related to the regenerated PET-based hybrid xerogel in the fields of electromagnetic shielding and photo-thermal conversion. Specifically, waste PET is dissolved with a trifluoroacetic acid / dichloromethane mixed solvent, functional nanofiller is dispersed, a poor solvent is added to induce PET to separate out crystals, hybrid gel is constructed, and the PET multifunctional hybrid xerogel is obtained through direct forced air drying. A mixed solution required by the PET-based hybrid xerogel is prepared from the following components in parts by weight: 5 to 20 parts of waste PET, 1 to 4 parts of functional nano filler Ni-coated CNT, 72 parts of trifluoroacetic acid / dichloromethane mixed solvent and 4 to 22 parts of poor solvent deionized water. In order to further strengthen the mechanical property and the photo-thermal storage capacity of the PET / Ni-coated CNT hybrid xerogel, a phase-change material polyethylene glycol (PEG) is covalently embedded into a foam structure of the hybrid xerogel, and the PET / Ni-coated CNT / PEG multifunctional composite material with good mechanical strength, excellent electromagnetic shielding performance and high photo-thermal energy storage is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of waste polyester upgrading and recycling, and in particular to a method for preparing a recycled PET-based hybrid xerogel and application of related PET-based multifunctional composite materials in the fields of electromagnetic shielding and photothermal conversion. Background Art

[0002] Polyethylene terephthalate (PET) is the polymer product with the largest single production capacity and output. It has been widely used in the textile industry, food packaging, electronic equipment, and automotive parts. According to industry forecasts, in 2024, my country's PET production capacity will be nearly 80 million tons, covering multiple categories such as PET fiber, PET base film, and bottle-grade PET. Therefore, there is an urgent need to increase the recycling rate of PET, improve its recycling and reuse technology, and realize the upgrading and recycling of PET.

[0003] At present, the recycling of polyethylene terephthalate (PET) mainly adopts the following methods: traditional recycling (including landfill and incineration), physical recycling and chemical recycling. Traditional recycling methods are difficult to degrade under natural conditions, which easily leads to the accumulation of microplastics and nanoplastics in the environment, posing a potential threat to human health (Chinese patent CN110864308A). Although chemical recycling is regarded as a cutting-edge technology that may replace traditional recycling, its process is complicated, its mechanism of action is not clear, and its reaction efficiency needs to be improved. It is still in the development stage (Chinese patents CN115103874A, CN118221520A, CN116606201A and CN115397905A, etc.). In contrast, physical recycling technology is relatively mature because of its simple process, low cost and no pollution during the reuse process. Through physical recycling, not only can the reuse scope of waste PET be expanded, but also multifunctional recycled PET composite materials can be prepared, thereby significantly improving the recycling rate of PET.

[0004] Some intellectual property rights have focused on the application of PET-based composite materials in the fields of photothermal conversion, radiation refrigeration, pollutant adsorption and electromagnetic shielding. For example, Chinese patent CN113603913A discloses a technology for preparing a photothermal conversion film, the film structure mainly includes carbon nanotubes and chitin, in which PET is only used as a supporting substrate, its own performance potential has not been fully utilized, and its application range is relatively narrow; Chinese patent CN116814046A discloses a PET-based electromagnetic shielding composite material prepared by melt blending of waste PET plastic, waste lead-acid battery positive electrode material and attapulgite. How to make PET-based composite materials have two or more functionalities at the same time and realize the maximum resource utilization of waste PET is the technical problem to be solved by the present invention. Summary of the invention

[0005] In view of the technical problems existing in the recycling of PET in the prior art, the purpose of the present invention is to provide a preparation method and application of a recycled PET-based hybrid dry gel prepared based on waste PET, so as to realize the physical upgrading and recycling of waste PET, alleviate and partially solve the environmental pollution problem of waste PET, and the prepared recycled PET-based hybrid dry gel has the advantages of high mechanical strength, good photothermal conversion efficiency and electromagnetic shielding effectiveness.

[0006] The first aspect of the present invention provides a method for preparing the above-mentioned PET-based hybrid xerogel.

[0007] The PET-based hybrid xerogel of the present invention is prepared by a method of dissolution crystallization inducing gelation. Specifically, waste PET and dispersed functional nanofillers are dissolved in a trifluoroacetic acid / dichloromethane mixed solvent, a poor solvent is added to induce PET to precipitate crystals, a hybrid gel is constructed, and PET multifunctional hybrid xerogel is obtained by direct air drying.

[0008] The components in the mixed solution required for the PET-based hybrid dry gel of the present invention include, by weight, 5 to 20 parts of waste PET, 1 to 4 parts of functional nano filler Ni@CNT, 72 parts of trifluoroacetic acid / dichloromethane mixed solvent, and 4 to 22 parts of poor solvent deionized water.

[0009] The waste PET used in the present invention is a highly transparent, low-color bottle polyester crushed material, and its intrinsic viscosity is 0.8-1.0 dL·g as measured by an Ubbelohde viscometer with reference to GB / T 14190-2017. -1 .

[0010] The present invention uses a trifluoroacetic acid / dichloromethane mixed solvent as a good solvent for waste PET, wherein the mass ratio of trifluoroacetic acid to dichloromethane is fixed at 2:1.

[0011] The functional nanofiller used in the present invention is Ni@CNT, preferably one of the nickel-coated multi-walled carbon nanotubes XFM52 (diameter 8-15 nm, length 50 μm), XFM55 (diameter 30-50 nm, length <10 μm) and XFM56 (diameter >50 nm, length <10 μm) produced by Xianfeng Nano Co., Ltd.

[0012] In the above technical solution, the functional nanofiller is uniformly dispersed in the mixed solution by physical mixing, including but not limited to any one or more combinations of magnetic stirring, ultrasonic dispersion, mechanical sand milling, etc.

[0013] In the above technical solution, deionized water is added to the above mixed solution at room temperature to induce PET dissolution and crystallization to generate an organic / inorganic hybrid gel, which is then air-dried to obtain a nanofiber skeleton and porous PET multifunctional hybrid xerogel. The deionized water needs to be added slowly drop by drop, and each addition needs to be fully mixed using a vortex mixer to eliminate local solute precipitation.

[0014] According to some preferred and specific aspects of the present invention, the drying is performed by direct air-blast drying, wherein the drying temperature is 50-70° C. and the drying time is 8 h-48 h.

[0015] In the present invention, the organic / inorganic hybrid jelly is a special dispersion system commonly known, which has no fluidity and often contains a large amount of liquid. Specifically, the hybrid jelly of the present invention is a three-dimensional network structure with PET nanofibers as the skeleton, and the nanofibers are filled with organic solvents as dispersion media. Ni@CNT is uniformly composited with PET nanofibers, and the three together constitute the organic / inorganic hybrid jelly.

[0016] Another technical solution provided by the present invention is about the application of the above-mentioned PET / Ni@CNT hybrid dry gel in the field of electromagnetic shielding and photothermal conversion.

[0017] At the same time, in order to further enhance the mechanical properties and photothermal storage capacity of the PET / Ni@CNT hybrid dry gel, the present invention covalently embeds the phase change material polyethylene glycol (PEG) into the hybrid dry gel pore structure to obtain a PET / Ni@CNT / PEG multifunctional composite material with good mechanical strength, excellent electromagnetic shielding performance and high photothermal energy storage.

[0018] The PET / Ni@CNT / PEG multifunctional composite material of the present invention comprises the following steps: firstly, the PET / Ni@CNT hybrid dry gel is surface treated so that its PET skeleton has active groups; then, the molten PEG phase change material is vacuum immersed, and polyisocyanate is used to achieve chemical bonding between the PEG and the PET skeleton.

[0019] In the present invention, the PET / Ni@CNT hybrid dry gel is surface treated with a sodium hydroxide / ethanol solution, so that active functional groups such as -OH and -COOH are exposed on the PET skeleton, and the PET / Ni@CNT hybrid dry gel is obtained by air drying. The concentration of the sodium hydroxide / ethanol solution is 0.5-2wt%, the treatment temperature is 30-70°C, and the treatment time is 30min-2h.

[0020] In the present invention, the phase change material PEG is used to covalently fill and activate the PET / Ni@CNT hybrid dry gel. A mixed solution of molten PEG, polyisocyanate and catalyst dibutyltin dilaurate (DBTDL) is prepared, wherein the PEG and polyisocyanate are fed according to a molar ratio of isocyanate to PEG terminal hydroxyl group of 2:1 to 4:1, and the mass fraction of DBTDL in the mixed solution is fixed at 0.5 parts.

[0021] The phase change material PEG used in the present invention has a molecular weight between 2000 and 10000, including but not limited to any one of PEG-2000 (molecular weight of 2000), PEG-6000 (molecular weight of 6000), and PEG-10000 (molecular weight of 10000).

[0022] The polyisocyanate used in the present invention includes, but is not limited to, any one of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI) and hexamethylene diisocyanate (HDI).

[0023] In the present invention, the activated PET / Ni@CNT hybrid dry gel is placed in the above-mentioned molten mixed solution, and vacuum is applied until the dry gel is completely immersed in the solution and no bubbles escape; the PET / Ni@CNT / PEG composite material is taken out, the surface not immersed in PEG is wiped off with filter paper, and the composite material is transferred to a forced air drying oven, and reacted at 70-90° C. for 8-24 hours to obtain a PET / Ni@CNT / PEG multifunctional composite material.

[0024] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: The present invention utilizes waste PET to prepare PET / Ni@CNT hybrid xerogel, and covalently bonds phase change materials to obtain PET / Ni@CNT / PEG multifunctional composite materials, thereby realizing the upgrading and recycling of waste PET.

[0025] The composite material prepared by the present invention integrates and coordinates the unique characteristics of polymer intrinsic properties, inorganic nanoparticle-polymer and polymer-polymer, realizes organic combination, and prepares a composite material with specific macroscopic and microscopic structures; The PET / Ni@CNT / PEG multifunctional composite material prepared by the present invention can well shield the electromagnetic waves in the X-band; The PET / Ni@CNT / PEG multifunctional composite material prepared by the present invention has high light-to-heat conversion efficiency and effectively stores thermal energy through phase change materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the hybrid xerogel of Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the multifunctional composite material of Example 1 of the present invention; Figure 3 These are digital photos of the multifunctional composite material of the embodiment of the present invention and comparative example 5 before and after heating. DETAILED DESCRIPTION

[0027] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0028] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art. Example 1

[0029] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 10g of PET waste plastic (with an intrinsic viscosity of 0.82dL·g -1 ), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 2g Ni@CNT (XFM55) was added to highly disperse; 16g deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid xerogel; Take 5 g of PET / Ni@CNT hybrid xerogel, place it in 50 g of sodium hydroxide / ethanol solution (1 wt%), wait until the hybrid xerogel is completely soaked, raise the temperature to 50 ° C, slowly stir for 1 h, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 9g of PEG-6000, 1g of IPDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1). Vacuum until the dry gel is completely immersed in the mixed melt and no bubbles escape. Take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80℃ oven, and continue the reaction for 12h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material.

[0030] The scanning electron microscopy image of the PET / Ni@CNT hybrid xerogel prepared in this example is shown in Figure 1 ; SEM images of PET / Ni@CNT / PEG multifunctional composite materials are shown in Figure 2 . Example 2

[0031] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 5g of PET waste plastic (with an intrinsic viscosity of 0.98dL·g -1 ), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 1g Ni@CNT (XFM52) was added to highly disperse; 22g deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid xerogel; Take 5 g of PET / Ni@CNT hybrid xerogel and place it in 50 g of sodium hydroxide / ethanol solution (0.5 wt%) until the hybrid xerogel is completely soaked, raise the temperature to 60 ° C, stir slowly for 30 min, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 6.8g of PEG-2000, 3.2g of HDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1). Vacuum until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to a 70℃ oven, and continue the reaction for 24h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material. Example 3

[0032] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 20g of PET waste plastic (with an intrinsic viscosity of 0.81dL·g -1), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 4g Ni@CNT (XFM52) was added to highly disperse; 4g deionized water was slowly added dropwise into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid xerogel; Take 5 g of PET / Ni@CNT hybrid xerogel and place it in 50 g of sodium hydroxide / ethanol solution (2 wt%) until the hybrid xerogel is completely soaked, raise the temperature to 40 °C, slowly stir for 2 h, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 9.3g of PEG-10000, 0.7g of MDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1). Vacuum until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to a 90℃ oven, and continue the reaction for 8h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material. Example 4

[0033] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 10g of PET waste plastic (with an intrinsic viscosity of 0.92dL·g -1 ), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 1g Ni@CNT (XFM56) was added to highly disperse; 17g deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid dry gel; Take 5 g of PET / Ni@CNT hybrid xerogel, place it in 50 g of sodium hydroxide / ethanol solution (1 wt%), wait until the hybrid xerogel is completely soaked, raise the temperature to 50 ° C, slowly stir for 1 h, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 9.2g of PEG-6000, 0.8g of TDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1), and evacuate until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80℃ oven, and continue the reaction for 12h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material. Example 5

[0034] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 10g of PET waste plastic (with an intrinsic viscosity of 0.92dL·g -1 ), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 4g Ni@CNT (XFM52) was added to highly disperse; 14g deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid dry gel; Take 5 g of PET / Ni@CNT hybrid xerogel, place it in 50 g of sodium hydroxide / ethanol solution (0.5 wt%), wait until the hybrid xerogel is completely soaked, raise the temperature to 60 ° C, slowly stir for 2 h, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 8.9g of PEG-6000, 1.1g of MDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1), and evacuate until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80℃ oven, and continue the reaction for 12h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material. Example 6

[0035] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 10g of PET waste plastic (with an intrinsic viscosity of 0.88dL·g -1), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 1g Ni@CNT (XFM52) was added to highly disperse; 17g deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid dry gel; Take 5 g of PET / Ni@CNT hybrid xerogel, place it in 50 g of sodium hydroxide / ethanol solution (2 wt%), wait until the hybrid xerogel is completely soaked, raise the temperature to 40 ° C, slowly stir for 30 min, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 9.3g of PEG-6000, 0.7g of IPDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 2:1). Vacuum until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80℃ oven, and continue the reaction for 12h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material. Example 7

[0036] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: 10g of PET waste plastic (with an intrinsic viscosity of 0.88dL·g -1 ), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 1g Ni@CNT (XFM56) was added to highly disperse; 17g deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid dry gel; Take 5 g of PET / Ni@CNT hybrid xerogel, place it in 50 g of sodium hydroxide / ethanol solution (0.5 wt%), wait until the hybrid xerogel is completely soaked, raise the temperature to 60 ° C, slowly stir for 2 h, take it out, and blow dry it to obtain activated PET / Ni@CNT hybrid xerogel; Take 1g of activated PET / Ni@CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 8.7g of PEG-6000, 1.3g of IPDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 4:1). Vacuum until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80℃ oven, and continue the reaction for 12h to obtain the corresponding PET / Ni@CNT / PEG multifunctional composite material. Comparative Example 1

[0037] This example provides a method for preparing PET xerogel. The preparation method comprises: 10g of PET waste plastic (with an intrinsic viscosity of 0.94dL·g -1 ), dissolved in a mixed solution of 48g of trifluoroacetic acid (TFA) and 24g of dichloromethane (DCM); 18g of deionized water was slowly added dropwise into the mixed solution and fully shaken, the obtained mixed solution containing PET was poured into a desired mold, sealed to prevent volatilization, placed at room temperature for 6 hours to form a gel, and air-dried to obtain a PET dry gel; Comparative Example 2

[0038] This example provides a method for preparing a PET xerogel and a corresponding PET / PEG multifunctional composite material. The preparation method comprises: The preparation method of PET dry gel is the same as that of Comparative Example 1.

[0039] Take 5 g of PET dry gel and place it in 50 g of sodium hydroxide / ethanol solution (2 wt%). When the dry gel is completely soaked, raise the temperature to 40°C, stir slowly for 30 min, take it out, and blow dry it to obtain activated PET dry gel. Take 1 g of activated PET dry gel and place it in 10 g of a mixed melt containing phase change material, wherein the mixed melt contains 9 g of PEG-6000, 1 g of IPDI and 50 mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1). Vacuum until the dry gel is completely immersed in the mixed melt and no bubbles escape. Take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80°C oven, and continue the reaction for 12 hours to obtain the corresponding PET / PEG multifunctional composite material. Comparative Example 3

[0040] This example provides a method for preparing a PET / CNT hybrid xerogel and a corresponding PET / CNT / PEG multifunctional composite material. The preparation method comprises: 10g of PET waste plastic (with an intrinsic viscosity of 0.82dL·g -1), dissolved in a mixed solution of 48g trifluoroacetic acid (TFA) and 24g dichloromethane (DCM), and after fully dissolved, 4g CNT (XFM07) was added to highly disperse; 16g deionized water was slowly dripped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain a PET / CNT hybrid dry gel; Take 5 g of PET / CNT hybrid xerogel, place it in 50 g of sodium hydroxide / ethanol solution (1 wt%), wait until the hybrid xerogel is completely soaked, raise the temperature to 50 ° C, slowly stir for 1 hour, take it out, and blow dry it to obtain activated PET / CNT hybrid xerogel; Take 1g of activated PET / CNT hybrid dry gel and place it in 10g of a mixed melt containing phase change material, wherein the mixed melt contains 9g of PEG-6000, 1g of IPDI and 50mg of DBTDL (the molar ratio of isocyanate to PEG terminal hydroxyl group is about 3:1), and evacuate until the dry gel is completely immersed in the mixed melt and no bubbles escape; take out the sample, wipe the mixed melt on its surface with filter paper, transfer the sample to an 80°C oven, and continue the reaction for 12h to obtain the corresponding PET / CNT / PEG multifunctional composite material. Comparative Example 4

[0041] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel. The preparation method includes: 10g of PET waste plastic (with an intrinsic viscosity of 0.86dL·g -1 ), dissolved in a mixed solution of 48g of trifluoroacetic acid (TFA) and 24g of dichloromethane (DCM), and after fully dissolved, 3g of Ni@CNT (XFM55) was added to highly disperse; 16g of deionized water was slowly dropped into the above mixed solution and fully shaken, and the obtained mixed solution containing PET / Ni@CNT was poured into the required mold, sealed to prevent volatilization, and placed at room temperature for 6h to form a gel, which was dried with air blast to obtain PET / Ni@CNT hybrid dry gel. Comparative Example 5

[0042] This example provides a method for preparing a PET / Ni@CNT hybrid xerogel and a corresponding PET / Ni@CNT / PEG multifunctional composite material. The preparation method includes: The preparation of activated PET / Ni@CNT hybrid xerogel was the same as in Example 1. 1 g of activated PET / Ni@CNT hybrid xerogel was placed in 10 g of molten PEG-6000.

[0043] The PET / Ni@CNT / PEG multifunctional composite materials of this example and Example 1 were placed in a 90°C blast drying oven at the same time. After heating for 1 hour, the digital photos were shown. Figure 3 .

[0044] The PET-based multifunctional composite materials prepared in Examples 1-7 and Comparative Examples 1-5 were subjected to performance tests. The compression strength was based on the national standard GB / T 8813-2020, and the relevant compression strength is shown in Table 1; the photothermal conversion efficiency was based on the method provided by Chinese patent CN117517391A, using a 1SUN light source (1kW·m -2 ) irradiate the surface of the composite material, use an infrared thermal imager to detect the surface of the sample until its surface temperature is higher than 80°C, and divide the phase change latent heat of PEG inside the sample (measured by differential calorimeter) by the solar radiation energy on the surface of the sample to be tested as the photothermal conversion efficiency. The relevant photothermal conversion efficiencies are listed in Table 1. For electromagnetic shielding performance, refer to the method provided by Chinese patent CN 109521458B, and use the coaxial method to test the shielding characteristics of the sample against X-band electromagnetic waves, wherein the total electromagnetic shielding efficiency at 9 GHz is listed in Table 1.

[0045] Table 1 Photothermal conversion efficiency and electromagnetic shielding performance of multifunctional composite materials of Examples 1 to 7 and Comparative Examples 1 to 5

[0046] Examples 1 to 3 illustrate the effect of the solid content of waste PET and Ni@CNT (mass ratio fixed at 5:1) in the mixed solution on the photothermal conversion efficiency and electromagnetic shielding performance of the corresponding multifunctional composite material; Examples 1, 4 and 5 illustrate the effects of the relative contents of waste PET and Ni@CNT on the light-to-heat conversion efficiency and electromagnetic shielding performance of the corresponding multifunctional composite materials; Examples 1, 6 and 7 illustrate the effect of the molar ratio of isocyanate to PEG terminal hydroxyl groups in the phase-change mixed melt on the light-to-heat conversion efficiency and electromagnetic shielding performance of the corresponding multifunctional composite materials; Comparative Examples 1 to 3 show that Ni@CNT is a key component for high functionalization of composite materials; Comparative Example 4 shows that filling the phase change material PEG is the key to the composite material having high light-to-heat conversion efficiency; Comparative Example 5 shows that polyisocyanate is a key component for the covalent embedding of the phase change material in the composite material, and the sample of Comparative Example 5 without polyisocyanate escapes from the phase change material after heating.

[0047] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0048] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A recycled PET-based hybrid xerogel, characterized in that: The method is prepared by using a recycled PET-based mixed solution through a dissolution crystallization-induced gelation method. The components of the recycled PET-based mixed solution are calculated by weight and include: 5 to 20 parts of waste PET, 1 to 4 parts of Ni@CNT, 72 parts of a trifluoroacetic acid / dichloromethane mixed solvent, and 4 to 22 parts of deionized water.

2. The recycled PET-based hybrid xerogel according to claim 1, characterized in that The waste PET is measured by an Ubbelohde viscometer with reference to GB / T 14190-2017 to have an intrinsic viscosity of 0.8-1.0 dL·g -1 .

3. The recycled PET-based hybrid xerogel according to claim 1, characterized in that The mass ratio of trifluoroacetic acid to dichloromethane in the trifluoroacetic acid / dichloromethane mixed solvent is 2:

1.

4. The recycled PET-based hybrid xerogel according to claim 1, characterized in that The Ni@CNT is any one of the nickel-coated multi-walled carbon nanotubes XFM52, XFM55, and XFM56 produced by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

5. The method for preparing the regenerated PET-based hybrid xerogel according to any one of claims 1 to 4, characterized in that: The method comprises the following specific steps: dissolving waste PET in a trifluoroacetic acid / dichloromethane mixed solvent, adding Ni@CNT and dispersing it evenly, adding deionized water dropwise and in portions to induce PET to precipitate and crystallize, constructing a hybrid gel, and directly drying the hybrid gel by air blowing, at a drying temperature of 50-70°C for 8h-48h, to obtain a PET hybrid dry gel.

6. A method for preparing a PET / Ni@CNT / PEG multifunctional composite material, characterized in that: The specific steps include: (1) surface treating the regenerated PET-based hybrid xerogel according to any one of claims 1 to 4 with a sodium hydroxide / ethanol solution to obtain an activated PET-based hybrid xerogel; (2) preparing a mixed solution of molten PEG, polyisocyanate and dibutyltin dilaurate (DBTDL); (3) placing the activated PET-based hybrid xerogel in the mixed solution of step (2) and applying vacuum until the xerogel is completely immersed in the mixed solution and no bubbles escape; taking it out, wiping off the surface solution, transferring it to a forced air drying oven, reacting it at 70-90°C for 8-24h, and obtaining a PET / Ni@CNT / PEG multifunctional composite material.

7. The method for preparing the PET / Ni@CNT / PEG multifunctional composite material according to claim 6, characterized in that: The concentration of the sodium hydroxide / ethanol solution in step (1) is 0.5-2 wt %; and / or the surface treatment temperature is 30-70° C., and the treatment time is 30 min-2 h.

8. The method for preparing the PET / Ni@CNT / PEG multifunctional composite material according to claim 6, characterized in that: The PEG and polyisocyanate are fed in a molar ratio of isocyanate to PEG terminal hydroxyl group of 2:1 to 4:

1.

9. The method for preparing the PET / Ni@CNT / PEG multifunctional composite material according to claim 6, characterized in that: The molecular weight of the PEG is 2000-10000; and / or the polyisocyanate is any one of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI) and hexamethylene diisocyanate (HDI).

10. Application of the PET-based hybrid xerogel according to any one of claims 1 to 4 or the PET / Ni@CNT / PEG multifunctional composite material prepared by the preparation method according to any one of claims 6 to 9 in the fields of electromagnetic shielding and photothermal conversion.